Penguatan Literasi Al-Qur’an Bagi Pelajar Desa Pakandangan Tengah Bluto Sumenep - Uswatun Hasanah; Muhammad Nurul Yaqin; Rosyidi (Jurnal Pengabdian Multidisiplin, 2024)
This Community Service Program (PkM) aims to strengthen Al-Qur'an literacy among students in Pakandangan Tengah Village, Bluto District, Sumenep Regency. Al-Qur'an literacy in this village is a major concern, considering the importance of the ability to read the Al-Qur'an, and the motivation to love the Al-Qur'an as part of character formation. This activity involves training in reading the Al-Qur'an using an easy-to-understand tajwid method and effective memorization techniques, as well as the ability to read the Al-Qur'an in a beautiful tone (Tartil Al-Qur'an). Active participation from schools, teachers and local community leaders also strengthens the implementation of this program. The results of the program show a significant increase in the ability to read the Al-Qur'an, with correct recitation knowledge and with beautiful tones (Tartil Al-Qur'an). It is hoped that this will be the first step in building a generation that is more knowledgeable in religious sciences and has strong moral values. Keywords: Literacy, Al-Qur'an, Students